STRATEGI PENGEMBANGAN USAHA DAUR ULANG SAMPAH PLASTIK DI BANK SAMPAH KOTA PEKALONGAN - Purwanto, Edy; Rahman Hakim, Miftahur (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: The Waste Bank is a waste collection concept with business management such as banking, but what is saved is the selected dry waste. The purpose of this study is to design an appropriate alternative strategy with a business model canvas approach for plastic waste recycling at BSKP. The research method used a qualitative descriptive approach with data analysis techniques using SWOT analysis and the business model canvas. The results showed that the development of a business model was prioritized on 4 blocks, namely key resources, key partners, key activities and customer relationships. The development of key resource blocks is carried out by increasing the skills and understanding of human resources regarding the use of technology and information. Development of key partner blocks by creating creative programs to improve relationships with partners, especially customers. Development of block key activities by establishing relationships with customers in the use of micro-scale plastic waste. Whereas in developing customer relationships, it is necessary to improve personal and group services by creating social media channels to maintain and communicate instinctively with customers and potential customers.Â Abstrak: Bank Sampah merupakan konsep pengumpulan sampah dengan manajemen usaha seperti perbankan namun yang ditabung merupakan sampah kering yang sudah dipilih. Tujuan penelitian ini yaitu merancang strategi alternatif yang tepat dengan pendekatan business model canvas usaha daur ulang sampah plastik di BSKP. Metode penelitian menggunakan pendekatan deskriptif kualitatif dengan Teknik analisis data menggunakan analisis SWOT dan business model canvas. Hasil penelitian menunjukkan dalam pengembangan model bisnis diprioritaskan pada 4 blok yaitu key resources, key partner, key activities dan customer relationship. Pengembangan pada blok key resources dilakukan dengan cara peningkatan ketrampilan dan pemahaman SDM tentang pemanfaatan teknologi dan informasi. Pengembangan pada blok key partner dengan membuat program yang kreatif dalam meningkatkan hubungan dengan mitra khususnya nasabah. Pengembangan pada blok key activities dengan cara menjalin hubungan dengan nasabah dalam pemanfaatan sampah plastik skala mikro. Sedangkan dalam pengembangan customer relationship perlu ditingkatkan dalam layanan personal maupun kelompok dengan membuat channel media sosial guna mempertahankan dan komunikasi yang instens dengan pelanggan dan calon pelangganÂ Garbage Bank, Plastic Waste, SWOT, Business Model Canvas